Computation of M-Polynomial and Topological Indices of Phenol Formaldehyde - Muhammad Kamran; Nadeem Salamat; Riaz Hussain Khan; Ubaid ur Rehman Asghar; Md. Ashraful Alam; M. K. Pandit (Journal of Chemistry)
Phenol formaldehyde (phenolic resin) has a wide range of moldings. However, it has immense consumption in manufacturing electrical equipment due to its insulating property. Phenolic resin retains properties at the freezing point, and also its age cannot be determined. Due to its insulator property, it has wide use in electrical equipment. In this article, degree-based topological indices of phenol formaldehyde are determined with the help of M-polynomial. We calculate the Zagreb index, Randić index, K-Banhatti indices, modified K-Banhatti indices, atom-bond connectivity index, geometric arithmetic index, symmetric index, inverse sum index, and harmonic index.